Developing the Web Portals of the German National Library of Science and Technology: Tools and Workflows Used - Strobel, Sven (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
Teams working on the development of software systems use certain tools and workflows of product and knowledge management. These tools and workflows help them plan, monitor and control the product at all stages of the product lifecycle as well as capture, develop and share project-related knowledge. This paper discusses the tools and workflows development teams of the German National Library of Science and Technology (TIB) use when developing the web portals. The use case illustrated here is a project, in which the interaction concept and screen design of the video portal of TIB (TIB|AV-Portal) had to be adapted to the new look and feel of the main portal (TIB-Portal). In the course of the project, the team gathered and structured preliminary requirements in the enterprise wiki, created an Axure user interface prototype, evaluated the prototype and specified the requirements using sprints from the Scrum framework, commissioned external screen designers and software developers to create a new screen design based on the prototype and implement the requirements, tested the implementations in a collaborative workflow and approved their deployment after debugging.